Scenedesmus obliquus: A Potential Natural Source for Cosmetic Industry - Sevilay Cengiz Sahin (International Journal of Secondary Metabolite)
Skin is the largest organ of our body and it protects interior organs against several environmental factors. Hyperpigmentation problem occurs as a result of abnormal melanin accumulation in the skin. A considerable amount of world’s population uses skin whitening products. It is known that various algae-derived secondary metabolites play an important role in skin problems. Therefore, the tyrosinase inhibitory activities of S. obliquus ethanol and water extracts were evaluated in the present study. Tyrosinase activity was determined spectrophotometrically at 492 nm. The ethanol extract showed the higher inhibitory activity on tyrosinase enzyme (IC50: 0.0270 g/mL) than water extract (IC50: 0.2882 g/mL). This result may have stemmed from the vanillic, ferulic acid and rutin components that were identified by RP-HPLC only in the ethanol extract.